Mechanochemical Synthesis and Structure of the Tetrahydrate and Mesoporous Anhydrous Metforminium(2+)-N,N'-1,4-Phenylenedioxalamic Acid (1:2) Salt: The Role of Hydrogen Bonding and n→π * Charge Assisted Interactions - Sayuri Chong-Canto; Efrén V. García-Báez; Francisco J. Martínez-Martínez; Angel A. Ramos-Organillo; Itzia I. Padilla-Martínez (MDPI AG, 2020)
A new organic salt of metformin, an antidiabetic drug, and N,N'-(1,4-phenylene)dioxalamic acid, was mechanochemically synthesized, purified by crystallization from solution and characterized by single X-ray crystallography. The structure revealed a salt-type crystal hydrate composed of one dicationic metformin unit, two monoanionic units of the acid and four water molecules, namely H2Mf(HpOXA)2∙4H2O. X-ray powder, IR, 13C-CPMAS, thermal and BET adsorption-desorption analyses were performed to elucidate the structure of the molecular and supramolecular structure of the anhydrous microcrystalline mesoporous solid H2Mf(HpOXA)2. The results suggest that their structures, conformation and hydrogen bonding schemes are very similar. To the best of our knowledge, the selective formation of the monoanion HpOXA−, as well as its structure in the solid, is herein reported for the first time. Regular O(δ−)∙∙∙C(δ), O(δ−)∙∙∙N+ and bifacial O(δ−)∙∙∙C(δ)∙∙∙O(δ−) of n→π * charge-assisted interactions are herein described in H2MfA organic salts which could be responsible of the interactions of metformin in biologic systems. The results support the participation of n→π * charge-assisted interactions independently, and not just as a short contact imposed by the geometric constraint due to the hydrogen bonding patterns.